Bases conceptuales de imaginarios sociales y su relación con la gestión de la comunicación digital en espacios culturales - Rodríguez Caguana, Tomás Humberto (2018)
The investigation problem of this work is: What theoretical perspectives are related to the interpretation of social imaginaries with the management of digital communication of a cultural space? Therefore, as a general objective the study looks forward to conceptualize the main theoretical aspects that relate to social imaginaries and their relationship with the administration of digital communication of cultural areas. This work assumes as an epistemological foundation for the phenomenology materialist since the subject-object relationship is framed in the sensitive and tangible components that activate the cultural interpretation of the individual. The tentative hypothesis of this work is the following: the theoretical perspectives that relate to the understanding of social imaginaries with the management of digital communication in a cultural space are the interactional approach and the multidisciplinary subject. Finally, the partial conclusions of this article interprets that the western tradition immediately hierarchizes any relationship between areas of knowledge and disciplines.